DAYA TERIMA DAN ANALISIS ZAT GIZI SNACK CHURROS SUBSTITUSI TEPUNG BIJI NANGKA (Artocarpus heterophyllus lamk) DAN TEPUNG IKAN BILIS (Mystacoleucus padangensis Bleeker) SEBAGAI PMT PADA BALITA UMUR 1-5 TAHUN - Sharvina Nurul Qalbi; Dahliansyah; Ikawati Sulistyaningsih (Media Gizi Khatulistiwa, 2025)
ACCEPTANCE AND ANALYSIS OF NUTRITIONAL CONTENT OF CHURROS SNACKS SUBSTITUTED WITH Jangka Seed Flour (Artocarpus heterophyllus lamk) AND BILIS FISH MEAL (Mystacoleucus Padangensis Bleeker) AS PMT IN TODDLER AGE 1-5 YEARS Abstract Providing Supplementary Food (PMT) is an effort to increase food intake so that it is sufficient and can achieve optimal nutritional value, the nutritional content in it contains sufficient energy, protein, macro and micronutrients, PMT is also easy to make from local food ingredients that are in accordance with local conditions. This study aims to determine the acceptability and nutritional content of churros snacks substituted for jackfruit seed flour (artocarpus heterophyllus lamk) and anchovies flour (mystacoleucus Padangensis bleeker) as PMT for toddlers aged 1-5 years. This method uses experimental research consisting of three formulations, namely (F1, F2, and F3). The test was carried out in 3 stages, namely organoleptic tests on 25 panelists to determine the panelists' receptivity to color, taste, aroma and texture, effectiveness index tests and nutritional content of carbohydrates, proteins, fats, water and ash, which were carried out on churros. The research results showed that the best value for the organoleptic effectiveness index was obtained in the third formulation (F3) with the percentage of jackfruit seed flour (60%) and anchovies flour (10%), with a carbohydrate content of 36.96%, fat 21.76%, protein 5, 93%, fiber 0.92%, ash 1.29%, and water 33.15%. There is an influence of substitution of jackfruit seed flour (Artocarpus Heterophyllus Lamk) and bilis fish meal (Mystacoleucus Padangensis Bleeker) on the color, taste, aroma and texture of churros as PMT for toddlers aged 1-5 years. Keyword : Supplementary Feeding (PMT), Churros, Jackfruit Seed Meal (Artocarpus Heterophyllus Lamk), Bilis Fish Meal (Mystacoleucus Padangensis Bleeker), Proximate Test